Analysis of ‘Khao Yai’ Pummelo Fruit to Estimate Nutrient Losses Through Crop Removal - Tongleaw, Sukhawat; Krisanapook , Krisana; Phavaphutanon, Lop (Agriculture and Natural Resources, 2012)
For a perennial fruit crop, knowing the amount of nutrients removed from the soil by the harvested fruit is essential for efﬁ cient nutrient management. Nitrogen (N), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg) within the fruit of mature seedless ‘Khao Yai’ pummelo harvested in January and April from orchards in Samut Songkhram province were analyzed. The results showed that the outer peel (ﬂ avedo) had the highest nutrient concentrations followed by the pulp (juice sacs) which had high N, P and K but had very low Ca and Mg. The white sponge-like inner peel (albedo) and segment membrane had low N, P and K concentrations but had high Ca and Mg. ‘Khao Yai’ pummelo fruit had high K content followed by N and Ca while Mg and P were accumulated in much lower concentrations. The average amounts of nutrient loss through crop removal for every 1,000 kg of fresh ‘Khao Yai’ pummelo fruit were 1.92 kg N, 0.27 kg P, 2.80 kg K, 1.16 kg Ca and 0.19 kg Mg, respectively. Fruit harvested in January and April had comparable nutrient content except for a slightly higher N and lower Mg content in the January crop. Seasonal variation of nutrient losses through crop removal was therefore determined by the difference in crop yield in each season.